Genomic, Lipidomic and Metabolomic Analysis of Cyclooxygenase-null Cells: Eicosanoid Storm, Cross Talk, and Compensation by COX-1 - Abul B.M.M.K. Islam; Mandar Dave; Sonia Amin; Roderick V. Jensen; Ashok R. Amin (Genomics, Proteomics & Bioinformatics, 2016)
The constitutively-expressed cyclooxygenase 1 (COX-1) and the inducible COX-2 are both involved in the conversion of arachidonic acid (AA) to prostaglandins (PGs). However, the functional roles of COX-1 at the cellular level remain unclear. We hypothesized that by comparing differential gene expression and eicosanoid metabolism in lung fibroblasts from wild-type (WT) mice and COX-2-/- or COX-1-/- mice may help address the functional roles of COX-1 in inflammation and other cellular functions. Compared to WT, the number of specifically-induced transcripts were altered descendingly as follows: COX-2-/- > COX-1-/- > WT + IL-1β. COX-1-/- or COX-2-/- cells shared about 50% of the induced transcripts with WT cells treated with IL-1β, respectively. An interactive “anti-inflammatory, proinflammatory, and redox-activated” signature in the protein–protein interactome map was observed in COX-2-/- cells. The augmented COX-1 mRNA (in COX-2-/- cells) was associated with the upregulation of mRNAs for glutathione S-transferase (GST), superoxide dismutase (SOD), NAD(P)H dehydrogenase quinone 1 (NQO1), aryl hydrocarbon receptor (AhR), peroxiredoxin, phospholipase, prostacyclin synthase, and prostaglandin E synthase, resulting in a significant increase in the levels of PGE2, PGD2, leukotriene B4 (LTB4), PGF1α, thromboxane B2 (TXB2), and PGF2α. The COX-1 plays a dominant role in shifting AA toward the LTB4 pathway and anti-inflammatory activities. Compared to WT, the upregulated COX-1 mRNA in COX-2-/- cells generated an “eicosanoid storm”. The genomic characteristics of COX-2-/- is similar to that of proinflammatory cells as observed in IL-1β induced WT cells. COX-1-/- and COX-2-/- cells exhibited compensation of various eicosanoids at the genomic and metabolic levels.